2017
DOI: 10.1186/s13063-017-2216-9
|View full text |Cite
|
Sign up to set email alerts
|

The LeucoPatch® system in the management of hard-to-heal diabetic foot ulcers: study protocol for a randomised controlled trial

Abstract: BackgroundDiabetic foot ulcers are a common and severe complication of diabetes mellitus. Standard treatment includes debridement, offloading, management of infection and revascularisation where appropriate, although healing times may be long. The LeucoPatch® device is used to generate an autologous platelet-rich fibrin and leucocyte wound dressing produced from the patient’s own venous blood by centrifugation, but without the addition of any reagents. The final product comprises a thin, circular patch compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Following their introduction, more studies have been published with detailed study methodologies, independent randomization, blinding, and standardization of usual care in multicentre studies. 38,161,180,235 This is encouraging and supports the long-held notion that the delivery of high-quality studies in this field is indeed feasible. 236 Despite this, the majority of the new articles reviewed was still at a moderate to high risk of bias.…”
Section: Quality Of Evidencesupporting
confidence: 60%
See 2 more Smart Citations
“…Following their introduction, more studies have been published with detailed study methodologies, independent randomization, blinding, and standardization of usual care in multicentre studies. 38,161,180,235 This is encouraging and supports the long-held notion that the delivery of high-quality studies in this field is indeed feasible. 236 Despite this, the majority of the new articles reviewed was still at a moderate to high risk of bias.…”
Section: Quality Of Evidencesupporting
confidence: 60%
“…The 21‐point assessment criteria developed jointly by the IWGDF and the European Wound Management Association to guide improvements in trial design and presentation of study findings were published in 2016. Following their introduction, more studies have been published with detailed study methodologies, independent randomization, blinding, and standardization of usual care in multicentre studies . This is encouraging and supports the long‐held notion that the delivery of high‐quality studies in this field is indeed feasible .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This was followed by an open multicentre clinical study of 41 patients with hard to heal DFU treated weekly with Leucopatch that showed 32% healing within 12 weeks and 54% within 20 weeks (Londahl et al, 2015). Currently, a recent randomized controlled clinical trial is running in the United Kingdom, Denmark, and Sweden on 269 patients with hard to heal DFU with the primary outcome set as percentage of ulcers healed within 20 weeks (Game et al, 2017). The outcome of this crucial study has yet to be reported.…”
Section: Hydrogels For Treatment Of Retinopathymentioning
confidence: 99%
“…Indeed, according to the United Kingdom National Diabetic Foot Audit, less than half of all new diabetic foot ulcers are healed by 12 weeks [4]. Even in specialized centers, healing rates for DFUs amount to 22-30% at 20 weeks [5,6].…”
mentioning
confidence: 99%